Ethics in Artificial Intelligence: A Philosophical Exploration - Dina Destari; Roya Zahir; Hendro Sukoco (Journal of Humanities Research Sustainability, 2025)
Background. Artificial intelligence (AI) has emerged as a transformative technology, bringing unprecedented opportunities and ethical challenges. The growing autonomy of AI systems raises questions about moral responsibility, bias, and social impact, which require a philosophical exploration to address these issues comprehensively. Purpose. This study aims to explore the ethical dimensions of AI by focusing on algorithmic bias, moral responsibility, and social impact. Through a philosophical lens, the research seeks to identify key challenges and propose frameworks to bridge the ethical gaps in AI development and implementation. Method. The research adopts a qualitative approach by analyzing 15 purposively selected academic sources. These include peer-reviewed journal articles, policy reports, and books discussing AI ethics. A conceptual framework was developed to evaluate algorithmic bias, moral responsibility, and social impact, using thematic analysis to synthesize insights from the literature. Results. The findings reveal that algorithmic bias stems from unrepresentative training data, reinforcing historical injustices. Moral responsibility in AI development becomes complex due to the involvement of multiple actors, requiring new ethical frameworks. AI's social impact, particularly on inequality and access, highlights the urgent need for regulations to mitigate negative effects. Case studies in recruitment, healthcare, and criminal justice systems illustrate the real-world implications of these issues. Conclusion. This study underscores the importance of integrating ethical considerations into AI design and deployment. Philosophical perspectives provide valuable insights into addressing algorithmic bias, defining moral responsibility, and understanding social impacts. Future research should focus on empirical studies and the development of global ethical regulations to guide AI use responsibly.